Are videogame training gains specific or general? - Oei, Adam C.; Patterson, Michael D. (Frontiers in Systems Neuroscience, 2014)
Many recent studies using healthy adults document enhancements in perception and cognition from playing commercial action videogames. Playing action games (e.g., Call of Duty, Medal of Honor) is associated with improved bottom-up lower-level information processing skills like visual-perceptual and attentional processes. One proposal states a general improvement in the ability to interpret and gather statistical information to predict future actions which then leads to better performance across different perceptual/attentional tasks. Another proposal claims all the tasks are separately trained in the action videogames because the action videogames and laboratory tasks contain similar demands. We review studies of action and non-action videogames to show support for the latter proposal. To explain transfer in action videogames, we argue that the perceptual and attention tasks share common demands with the trained videogames (e.g., multiple object tracking, rapid attentional switches, and peripheral vision). In non-action videogames, several studies also demonstrate specific, limited transfer. One instance of specific transfer is the specific enhancement to mental rotation after training in games with a spatial emphasis (e.g, Tetris). In contrast, the evidence for transfer is equivocal where the game and task do not share common demands (e.g., executive functioning). Thus, the “common demands” hypothesis of transfer not only characterizes transfer effects in action videogames, but also non-action games. Furthermore, such a theory provides specific predictions, which can help in the selection of games to train human cognition as well as in the design of videogames purposed for human cognitive and perceptual enhancement. Finally this hypothesis is consistent with the cognitive training literature where most post-training gains are for tasks similar to the training rather than general, non-specific improvements.